Clobetasol propionate 0.025% cream in the management of steroid responsive dermatoses: an expert opinion - Thomas, Jayakar; Saraswat, Abir; Aurangabadkar, Sanjeev; Rathod, Roheet; Rathod, Rahul; Mane, Amey (International Journal of Research in Dermatology, 2022)
Topical corticosteroids play a key role in managing steroid responsive dermatoses (SRD). Current topical corticosteroid therapies are associated with various disadvantages. The current consensus article aims at providing a collation of evidence-based literature and clinical insights of the experts, regarding the efficacy, safety and usage of clobetasol propionate (CP) 0.025% cream in the management of SRD like plaque psoriasis. Clinical evidences suggest that the novel formulation of CP 0.025% cream has comparable efficacy and a better safety profile vs CP 0.05% cream in the management of plaque psoriasis. According to the doctors' experience, CP 0.025% can be used as first-line treatment for the management of SRD. In children 12-18-year-olds, CP 0.025% may be used cautiously, considering risk-benefit ratio. CP 0.025% may also be used as a maintenance therapy, after disease is brought under control with systemic therapy. Using moisturisers, salicylic acid, calcipotriol or tacrolimus as concomitant therapy with CP 0.025% cream may be beneficial in the management of SRD. In various comorbidities like diabetes and hypertension, CP 0.025% cream may be a better alternative verses CP 0.05% cream. Clinical evidences and experts suggest that for management of SRD, clobetasol propionate 0.025% cream can be recommended as a formulation with comparable efficacy and better safety profile versus CP 0.05% cream.